1999
DOI: 10.1542/peds.103.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Motor Development of Cocaine-exposed Children at Age Two Years

Abstract: Objective-This article was designed to investigate effects of prenatal cocaine exposure on motor development of young children from a predominately underprivileged, urban population.Methodology-A total of 260 infants and young children were initially recruited from either the newborn nursery or the at-risk pediatric clinic of an urban teaching hospital. Prenatal history and birth outcomes were collected from medical records. Demographic characteristics and additional drug histories were obtained from the mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 40 publications
6
40
1
1
Order By: Relevance
“…72,73 The PDI effect reported here was also similar to prenatal maternal smoking effects on 2-year PDI scores, risk of motor delay, balance, and fine-motor coordination at 5 years of age, as measured with the Peabody Developmental Motor Scales. 74 Motor effects may persist even when adjusted for birth weight, despite the fact that lower birth weight itself has been associated with increased frequency of motor problems.…”
Section: Discussionsupporting
confidence: 71%
“…72,73 The PDI effect reported here was also similar to prenatal maternal smoking effects on 2-year PDI scores, risk of motor delay, balance, and fine-motor coordination at 5 years of age, as measured with the Peabody Developmental Motor Scales. 74 Motor effects may persist even when adjusted for birth weight, despite the fact that lower birth weight itself has been associated with increased frequency of motor problems.…”
Section: Discussionsupporting
confidence: 71%
“…Most investigators have also not found detrimental effects of PCE on infant motor development, as measured by the Psychomotor Development Index (PDI) of the BSID or by the Peabody Developmental Motor Scales [2][3][4]12,13,21,34,36,41,43,[58][59][60]65,83]. By contrast, Singer et al [82] found that PCE was associated with lower PDI scores at about 17 months.…”
Section: Introductionmentioning
confidence: 99%
“…Uma boa parte desses estudos procurou determinar a influência de vários fatores de risco de ordem biológica e ambiental no desenvolvimento da criança (ANGELSEN;JACOBSEN;BAKKETEIG, 2001;ARENDT et al, 1999;EVENSEN et al, 2009;FETTERS;TRONICK, 1996;MAJNEMER;BARR, 2006;MILLER-LONCAR et al, 2005;GOYEN; R. da Educação Física/UEM Maringá, v. 22, n. 4, p. 511-521, 4. trim. 2011 LUI, 2002;NELSON et al, 2004;TRASTI et al, 1999;SOMMERFELT et al, 2002;RODRIGUES, 2005;SANTOS, 2009 A versão portuguesa das PDMS-2 foi aplicada a uma amostra de 540 crianças pré-escolares, com o objetivo de testar a sua equivalência psicométrica.…”
Section: Introductionunclassified